2016
DOI: 10.1177/0892020616637232
|View full text |Cite
|
Sign up to set email alerts
|

The challenges facing further education college governors in England

Abstract: ‘Further education’ (FE) is a substantial sector in the education system in England. It has funding of approximately £8 billion annually and educates close to three million students. Within the sector are 231 FE colleges which provide a range of courses that are typically vocational/skills-based. They vary in scale and scope with the largest colleges having a turnover in excess of £100 million and over 15,000 students. For a variety of reasons, the FE sector is experiencing various pressures which are presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…To close this aspect of the review, the corporate governance literature pertaining to English Further Education Colleges is now discussed. Several studies have found that non-executive board members of colleges realise that ensuring the financial sustainability of these non-profit (Sala, 2003) institutions is a key governance task (Hill et al, 2016;Masunga;. However, Gleeson (et al, 2011;and Shain, 1999) highlight that a focus upon the control of finance is not always considered to be good governance practice and that boards should give greater attention to the core business of teaching than to financial control.…”
Section: The Intersection Of Corporate Governance and Management Accomentioning
confidence: 99%
See 2 more Smart Citations
“…To close this aspect of the review, the corporate governance literature pertaining to English Further Education Colleges is now discussed. Several studies have found that non-executive board members of colleges realise that ensuring the financial sustainability of these non-profit (Sala, 2003) institutions is a key governance task (Hill et al, 2016;Masunga;. However, Gleeson (et al, 2011;and Shain, 1999) highlight that a focus upon the control of finance is not always considered to be good governance practice and that boards should give greater attention to the core business of teaching than to financial control.…”
Section: The Intersection Of Corporate Governance and Management Accomentioning
confidence: 99%
“…The organisation studied was an English Further Education ('FE') college. FE is an important sector in England, turning over more than £8 billion per annum and training approximately three million people each year (Hill et al, 2016). FE has a vocational focus and is located between statutory schooling and higher education.…”
Section: The Case Study Sector and Organisationmentioning
confidence: 99%
See 1 more Smart Citation
“…This competitive environment, coupled with political and financial uncertainty, steers the practice of college governance towards managing the huge risks, most of which are financial, associated with failing to 'get it right'. Although this threat is very real, in part due to the ever-increasing scrutiny and 'intervention' by the FE Commissioner (Hill, James, and Forrest 2016;J Burke 2018), the changing shape of governance in recent years has nevertheless been to the perceived detriment of those who are working at the 'chalk-face' (Hill 2000;Gleeson, Abbott, and Hill 2011); a shift that has been described as a move from trust to 'mistrust' by Thompson and Wolstencroft (2018). They argue that FE leaders have little say in the direction of their organisations due to heavy-handed political influence over vocational education strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The declining financial health of the FE sector and the recent programme of Government-led area reviews (O’Leary, 2016) has resulted in an increase in the number of mergers across the sector, where two colleges join together for financial or quality reasons. In their work on FE college governance, Hill et al (2016: 79) identify ten key challenges which they consider to be ‘significant, substantial, simultaneous and synergistic’ relating to the turbulent nature of the FE sector, the need to secure improvements in learner outcomes, and the cost of resourcing provision. In addition, employer-led reforms require managers to liaise and network across a wide range of stakeholders.…”
Section: Introductionmentioning
confidence: 99%